THE EFFECT OF USING SPOTIFY APPLICATION TOWARDS STUDENT’S LISTENING SKILL: (An Experimental Study at Eleventh Grade Student of SMAN 1 Cihara Lebak, Banten in Academic year 2023/2024) - Sri Lisda Ayu Bustomi (Cahaya Ilmu Bangsa Institute, 2024)
This research paper aims to investigate the significant effect of Spotify application on listening skills in eleven students of SMAN 1 Cihara Lebak-Banten in the academic year 2023/2024). This study used a quantitative approach and a quasi-experimental design. This study was conducted from May to June, and researchers have selected two classes as control and experimental classes. The technique in selecting samples is to use purposive sampling, researchers use class XI IPA 1 (32 students) as the control class and XI IPA 2 (32 students) as the experimental class. and to analyze the data researchers used SPSS 25 statistical calculations and used the post-test and pre-test values of the control and experimental classes to analyze hypothesis testing. Researchers get the results of t count (-13.900) with a two-sided significance value = 0.001 < α 0.05. therefore researchers conclude that the Spotify application has an effect on students' Listening skills.